Xanthomonas campestris pv. sesami에 의한 참깨의 세균성잎마름병 - 이승돈(Seungdon Lee); 이정희(Junghee Lee); 김용기(Yong-Ki Kim); 허성기(Sunggi Heu); 나동수(Dong-Soo Ra) (Sigmulbyeong yeon'gu, 2005)
A new bacterial disease of sesame(Sesamum indicum) was observed on field-grown plants in Suwon, Hongchun and Yeonchun in 2000. Leaf symptoms initially appeared as water-soaked spots that gradually enlarged, became necrotic and were often bordered by a small zone of lemon yellow tissue. In the case of severe infection, dead leaves were defoliated. Isolations made from diseased leaves on yeast extract dextrose calcium carbonate agar yielded nearly pure cultures of a yellow-pigmented bacterium typical of a xanthomonad. Two bacterial strains were purified and used for farther tests. Pathogenicity of strains was confirmed on 3-week-old sesame plants sprayed with bacterial suspensions containing $10^{8}cfu/ml$ of phosphate buffered saline. The Biolog and fatty acid analyses of the two strains(SL3451 and SL3476) 1mm sesame leaf blight showed that they could be identified as ft campestris pv. sesami because of their high similarity to the tester strain(X. campestris pv. sesami LMG865) with a match probability of $100%$. The bacterium grew well between 18 and 36$^{°}C$, but optimum temperature was $27^{°}C$ on LB broth. This is the first report of bacterial blight of sesame in Korea. Symptoms of bacterial blight of sesame are difficult to differentiated with those of bacterial leaf spot caused by Pseudomonas syringae pv. sesami. 2000년 수원, 홍천, 연천 지역의 참깨 포장에서 새로운 병해가 발견되었다. 처음에는 잎에 수침상의 작은 점무늬를 형성하다가 점점 커져 괴사가 일어나고 주위로 황화되었다. 심하게 감염된 경우는 병든 잎은 떨어졌다. YDC 배지에서 병원세균을 순수 분리 하였을 때 Xanthomonas 속 세균의 전형적인 특징인 노란색 색소를 띤 세균이 형성되었다. 분리된 세균을 $10^{8}cfu/ml$로 현탁한 후 3주 동안 자란 참깨 잎에 분무 접종하였을 때 처음과 같은 증상이 재현되었다. 분리된 세균은 대조균주 X. campestris pv. sesami LMG865와 지방산 조성 및 다양한 탄소원 이용정도를 이용하여 비교하였을 때 $100%$의 가능성으로 X. campestris pv. sesami로 동정되었다. 분리된 병원균은 $18\~36^{°}C$에서 생장이 양호하였으며, $27^{°}C$에서 가장 우수하였다. 이 보고는 국내에서 참깨의 세균성잎마름병 최초 보고이며, P. syringae pv. sesami에 의한 세균성점무늬병과 외부적인 병징으로 구별하기가 매우 어렵다.